Development of Gamification-Based Flipped Learning in Mathematics Learning as an Effort to Overcome Learning Obstacles - Zam Zam Jamaludin; Syifa Unnafsyah; Eva Silvia Agustin; Asep Nuryadin; Muhammad Rijal Wahid Muharram (Indonesian Journal of Primary Education, 2022)
The purpose this research was motivated because students experienced obstacles in learning mathematics in the Covid-19 Pandemic Era which affected learning outcomes. In addition, student activities in playing online games cause students to have no motivation to learn. This study aims to produce a digital learning design, namely gamification-based flipped learning and determine its feasibility. The research method was carried out using the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation) in mathematics, especially the Building Space material in Class V. In this study, data were collected through questionnaires, which were then analyzed by using two paired sample t-tests. The results of this study stated that the learning tools developed were appropriate both in terms of the Lesson Plan (RPP), Student Worksheets (LKPD), and learning evaluation instruments as well as comparisons of learning outcomes before using gamification-based flipped learning and learning after using flipped learning-based learning. gamification so that the development of gamification-based flipped learning in mathematics learning is valid, practical, and can be used to overcome learning obstacles experienced by students